2009
DOI: 10.1080/08039480902759192
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mental disorders in subjects with intellectual disability in the Lundby cohort 1947–97

Abstract: The Lundby Study is a prospective cohort study, which has followed a Swedish unselected community sample between 1 July 1947 and 1 July 1997. The aim was to study the risks of mental morbidity and different DSM-IV disorders in subjects with intellectual disability (ID) in the Lundby cohort between 1 July 1947 to 30 June 1997. The diagnosis of ID was re-evaluated according to DSM-IV in subjects who had been considered to have ID between 1947 and 1997. Multiple sources of information were used to obtain best est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…People with intellectual disability (ID) have a higher risk for psychiatric disorders than the general population [1, 2]. Thus, in a setting where people with ID have access to health care on the same terms as the general population, a higher psychiatric care utilization would be expected.…”
Section: Introductionmentioning
confidence: 99%
“…People with intellectual disability (ID) have a higher risk for psychiatric disorders than the general population [1, 2]. Thus, in a setting where people with ID have access to health care on the same terms as the general population, a higher psychiatric care utilization would be expected.…”
Section: Introductionmentioning
confidence: 99%
“…In the Lundby cohort, the cumulative incidence of psychotic disorders was 8%, which is significantly higher than in the general population. 12 In this study, psychiatric disorders, including schizophrenia, were more prevalent in individuals with mild than in those with moderate intellectual disability. In another study specifically designed to compare the rate of psychopathology in 2 community groups with varying degrees of intellectual disability, it was reported that psychotic disorders were significantly overrepresented in patients with mild/moderate than in those with severe/profound intellectual deficits.…”
mentioning
confidence: 58%
“…Individuals with intellectual disability (IQ < 70) are at higher risk of schizophrenia and other psychotic disorders than the general population (Bouras 2004;Nettelbladt 2009), with pregnancy and birth complications likely to be relevant aetiological factors in psychosis (O'Dwyer 1997). Diagnosis benefits from specialist input from intellectual disability services, and shared care is essential in achieving good outcomes.…”
Section: Intellectual Disabilitymentioning
confidence: 99%